Plasma-assisted machining characteristics of wire arc additive manufactured stainless steel with different deposition directions - Seong-Gyu Kim; Choon-Man Lee; Dong-Hyeon Kim (Journal of Materials Research and Technology, 2021)
With the development of additive manufacturing (AM) technology, many studies on wire arc additive manufacturing (WAAM) have been conducted due to its low production costs and high fabrication speed. Degree of freedom of the shape is a limitation of conventional machining (CM) that can be overcome by WAAM. Owing to the low level of shape completeness and surface roughness, post-processing through machining is needed. Plasma-assisted machining (PAM) is an effective method that improves the machinability of difficult-to-cut materials by softening the material by preheating using a heat source. In this study, CM and PAM of 304 stainless steel (SS) manufactured using WAAM were explored. Each 304 SS workpiece was manufactured using WAAM in X, Y, and Z directions. The experimental results were evaluated by conducting tensile tests and performing microstructural analysis. The machining conditions for PAM were selected via thermal analysis. Moreover, the post-machining effect was analyzed by measuring the cutting force, surface roughness, hardness, and microstructure. In addition, CM and PAM of 304 SS manufactured by casting were performed to compare the machining characteristics with those of the workpieces manufactured using WAAM.